PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE STAD (STUDENT TEAMS ACIEVEMENT DIVISION) UNTUK SISWA KELAS V SDN 007 SAMARINDA ULU TAHUN PEMBELAJARAN 2024/2025 - Anggun Amalia Arsanti; Iksam; Yudo Dwiyono; Sukriadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this research is the low learning outcomes of fifth-grade students at SDN 007 Samarinda Ulu, especially in the Pancasila Education subject. This research aims to determine the improvement in student learning outcomes through the STAD type Cooperative Learning model in fifth-grade students of SDN 007 Samarinda Ulu in the 2024/2025 Academic Year. The type of research used is Classroom Action Research (CAR) which consists of 2 cycles and each cycle consists of 2 meetings. The subjects in this study were 18 fifth grade students consisting of 8 male students and 10 female students. And the object of this research is the learning outcomes of Pancasila Education and the improvement of each cycle using the Cooperative Learning model. Data collection techniques in this study used observation, tests and documentation. The instruments in this study used teacher activity observation sheets, student activity observation sheets and evaluation tests. The data analysis techniques in this study used averages, percentages and diagrams. The research results showed that the increase was indicated by the learning outcomes of students in the pre-cycle obtaining an average of 54.6 with a completion percentage of 22%. The learning outcomes of students in cycle I experienced an increase of 16% from the pre-cycle baseline value, with an average class value of 63.33 with a completion percentage of 44%. The learning outcomes of cycle II experienced an increase of 37.86% from the pre-cycle baseline value, with an average class value of 75.27 with a completion percentage of 83% with 15 students completing and 3 students not completing, and achieving more than the expected success indicator of 70%. Based on the research results, it can be concluded that there was an increase in the learning outcomes of Pancasila Education on the material of Gotong Royong, Characteristics of My Nation through the Cooperative Learning model in grade V students of SDN 007 Samarinda Ulu in the 2024/2025 academic year.